Mapping Black Europe Monuments, Markers, Memories - Kelly, Natasha A.; Vassell, Olive (transcript Verlag, 2023)
Black communities have been making major contributions to Europe's social and cultural life and landscapes for centuries. However, their achievements largely remain unrecognized by the dominant societies, as their perspectives are excluded from traditional modes of marking public memory. For the first time in European history, leading Black scholars and activists examine this issue - with first-hand knowledge of the eight European capitals in which they live. Highlighting existing monuments, memorials, and urban markers they discuss collective narratives, outline community action, and introduce people and places relevant to Black European history, which continues to be obscured today.